The art of Tracey Emin - Merck, Mandy; Townsend, Chris; Emin, Tracey 1963- (Thames & Hudson Inc., 2002)
The career of Tracey Emin, one of the best-known contemporary British artists, has become a potent symbol of the relationship between art and celebrity in our time. When it was exhibited in London at the Tate in 1999, her now notorious installation My Bed was denounced by conservative critics as a scandal, but this and her other work have continued to attract ever larger audiences. Whether storming out of live television debates, talking about her abortions or modeling evening gowns for Vivienne Westwood, Tracey Emin makes headlines.